2020
DOI: 10.2147/ccide.s240212
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diabetes Related Knowledge, Attitudes and Practice – A Survey Among Oral Health Professionals in Victoria, Australia</p>

Abstract: Purpose: Until now, little is known as to how well the evidence supporting the link between periodontal disease and diabetes is incorporated in the dental practice, in Australia. This study aims to explore Oral health Professionals (OHP) knowledge, attitudes, and practice (KAP) towards diabetes screening in the dental setting. Methods: The survey questionnaire consisted of sociodemographic, practice characteristics and Likert scaled questions categorised in different domains of KAP and one additional domain as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…A study in Australia found that oral health professionals demonstrated adequate knowledge of diabetes-related oral health complications (≈86%) [10]. In contrast, Omani diabetic participants in the present study demonstrated lower levels of knowledge.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A study in Australia found that oral health professionals demonstrated adequate knowledge of diabetes-related oral health complications (≈86%) [10]. In contrast, Omani diabetic participants in the present study demonstrated lower levels of knowledge.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, the majority of patients with diabetes were found to have poor knowledge and awareness of oral health. In contrast, other studies conducted around the world have shown varying levels of knowledge of oral health among diabetics [10][11][12][13].…”
Section: Discussionmentioning
confidence: 75%